The Effect of Aqueous Garlic Extract on Interleukin-12 and 10 Levels in Leishmania major (MRHO/IR/75/ER) Infected Macrophages - MJ Gharavi; M Nobakht; S Khademvatan; F Fani; M Bakhshayesh; M Roozbehani (Tehran University of Medical Sciences, 2011)
Background: The aim of the present study was to investigate the immunomodulation effects of aqueous garlic extract (AGE) in the cultured macrophages infected by Leishmania major. Methods: After J774 macrophages proliferation in RPMI1640 and incubation with Leishmania for 72 hours, AGE was added in doses of 9.25, 18.5, 37, 74 and 148 mg/ml for 18, 24 and 48 hours and cell culture supernatants were harvested. The Leishmania infected J774 cells to assess the cell viability was examined using trypan blue and methylthiazol tetrazolium assay (MTT). An enzyme-linked immunosorbent assay (ELISA) was performed on cell culture supernatants for measurement of interleukin IL-10 and IL-12. Results: Dose of 37 mg/ml for 48 hours of garlic extract was the most potent dose for activation of amastigotes infected macrophages. In addition, AGE increased the level of IL-12 in Leishmania infected cell lines significantly. Conclusions: AGE treated cell is effective against parasitic pathogens, and AGE induced IL-12 differentially affected the immune response to invading Leishmania parasites.